(untitled) (Journal of Parents and Teachers, 1996)
The School for Parents of La Salle School of Sestao promotes collaboration between family and school, emphasizing that education begins at home. It offers a training program that includes an initial course, conferences and meetings for parents and educators. It seeks an integral and effective formation to improve the educational experience of the students.